We Care Programme: Uplift and Educational Support at Bondulu Children’s Home Toboh, Tambunan, Sabah, Malaysia - Wong Sing Yun; Suddin Lada; Brahim Chekima; Siti Nor Bayaah Ahmad; Rudy Ansar; Faerozh Madli; Mat Salleh Ayub (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2023)
ABSTRACT Purpose - This Community Project’s major goal is to uplift and provide educational support to the underprivileged students in the Needy Children’s Home of Bondulu, Toboh Tambunan. This initiative also aims to motivate and encourage the students to attain a higher level of educational achievement. Methods – Conducting workshops and motivation sessions on educational support to students in need. Through such sessions, students are shared with important information such as courses offered, course entry requirements, career opportunities, etc. Next, interactive activities are carried out to encourage students’ participation and to obtain intuitive education-related information from the students’. Result and discussions – Students from the Needy Home are better informed of the courses offered, the entry requirements and the career pathway available. They become highly motivated as they are exposed to the educational opportunities available to them upon completing their secondary education. Conclusion – In conclusion, the community project achieved its objectives in increasing the student’s knowledge of the education opportunities available to them and to be highly motivated to continue to a higher education level. Besides that, this project also helps the students to build higher self-esteem and to become highly motivated in pursuing higher education. This will assist the achievement of the Sustainable Development Goal (SDG) 4 which aims at ensuring equal access to all levels of education for the vulnerable.